PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP TINDAKAN PAJAK AGRESIF PADA PERUSAHAAN MANUFAKTUR - Fahriani, Melinda; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of good corporate governance (board of commissioners, board of directors, independent commissioner, and audit committee) to the action of aggressive tax which is measured by using effective tax rates on the manufacturing companies which are listed in Indonesia Stock Exchange.The population is all companies which are listed in Indonesia Stock Exchange. The samples are manufacturing companies which are listed in Indonesia Stock Exchange in 2009-2013 periods. 21 manufacturing companies have been determined as samples by using purposive sampling. The multiple regressions analysis technique is used as the research analysis technique. The classic assumption test has been done before the data is processed. The result of test shows that there is no heteroscedasticity, autocorrelation, and multicolonearity.The result of good corporate governance test to the action of aggressive tax shows that the board of commissioners, board of directors, and independent commissioners show that the existence of influence to the action of aggressive tax. Meanwhile, the audit committee does not have any influence to the action of aggressive tax which has been conducted by the company.Keywords: Good Corporate Governance, Effective tax rates, The Action of Aggressive Tax.